2015
DOI: 10.1002/admi.201500034
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Antifouling of Catalytic Pores Armed with Oxygenic Polyoxometalates

Abstract: A novel stimuli-responsive strategy against the irreversible fouling of porous materials and surfaces is presented herein. This is based on the molecular design of catalytic pore walls that foster a chemo-mechanical, self-cleaning behavior under neutral pH and mild conditions of pressure and temperature. This approach builds on bioinspired remediation mechanisms involving natural catalase enzymes for H2O2 dismutation and endogenous oxygen production. It is thus demonstrated that a very efficient antifouling ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…12). The stability of the fibril and ribbon-like morphology has been confirmed by TEM analysis after catalytic oxygen evolution, 38 which is consistent with the expected mechanical and hydrolytic robustness of the nano-assembly, 126,127 thus opening up a new perspective of engineered bio-hybrid anodes for electrocatalytic water oxidation.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…12). The stability of the fibril and ribbon-like morphology has been confirmed by TEM analysis after catalytic oxygen evolution, 38 which is consistent with the expected mechanical and hydrolytic robustness of the nano-assembly, 126,127 thus opening up a new perspective of engineered bio-hybrid anodes for electrocatalytic water oxidation.…”
Section: Discussionsupporting
confidence: 64%
“…[123][124][125] On the other hand, oxygenic POMs have been immobilized into polymeric membranes and polymeric multilayered capsules, to yield functional materials on a micro-scale arrangement. 126,127 Building on these results, we have very recently reported the assembly of the POM {Ru 4 (m-OH) 2 (m-O) 4 (H 2 O) 4 [g-SiW 10 O 36 ]} 10À on TMV, previously coated with polyallylamine hydrochloride (PAH) and 5,10,15,20-tetrakis (1-methyl-4-pyridinium) porphyrin (HTMPyP). The supramolecular conjugate is formed by the electrostatic capture of the polyanionic catalyst on the cationized viral surface (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Previous theoretical studies have demonstrated that increasing the diameter of the CNTs results in an adverse effect on the salt rejection efficiency. [ 20–102 ] Appropriate pore diameters act as energy barriers at the channel entries, allowing water to pass through the hollow channels while salt ions are rejected. [ 103 ] Computational studies conducted by Corry et al suggested that the ideal CNT diameter to achieve high water permeability and salt rejection should be <0.6 nm.…”
Section: Water Treatment Applications Of Cnt‐based Membranesmentioning
confidence: 99%
“…[26] More recently, catalytic antifouling response has been observed in porous materials through novel chemomechanical strategies that inhibit the fouling of the membrane via selfcleaning. [27,28] For this purpose, the surface pores are armed with oxygen evolving water oxidation catalysts based on polyoxometalates, [29] that help to create nascent oxygen bubbles in the presence of hydrogen peroxide as chemical trigger, inducing the displacement of the foulants that reach out the surface of the porous architecture guaranteeing a long-term efficiency of the material. Furthermore, through the assembly of an oxygen evolving polyoxometalate cluster with tailored MWCNTs an improvement in the oxygen-evolving activity was achieved, thanks to the sequential electron transfer to the electrode that favour energy dispersion and relieve catalytic fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…The membrane formation mechanism of amphiphilic polymers in the conventional non-solvent-induced phase separation (NIPS) processes has been employed for creating lithium-ion-conducting channels. While an amphiphilic copolymer is utilized for the fabrication of porous membranes in the NIPS process with water as a coagulant, the hydrophilic segments of the copolymer move toward the water-rich phase to be retained at the pore surfaces of the resulting porous membrane. , This approach has been widely applied to the preparation of porous membranes with functional polymer segments at the pore surfaces showing antifouling characteristics, , catalytic ability, and stimuli-responsive gating features. , Based on the previous literature on porous membrane preparation, poly­(ethylene glycol) (PEG) has been chosen as the hydrophilic segment. In addition to the hydrophilicity, PEG also shows high solvation efficiency with liquid electrolytes for GPEs and high affinity to as well as transporting ability of lithium ions. Hence, the PEG segments residing at the pore walls of the porous membranes of GPEs could contribute to the creation of continuous PEG-rich channels in the membrane pores for lithium-ion conduction.…”
Section: Introductionmentioning
confidence: 99%